TOWARDS A FINANCIAL-INDUSTRIAL SYNERGY: AN EMPIRICAL ANALYSIS OF THE REAL ECONOMY AND BANKING SECTOR LINKAGES IN UZBEKISTAN - Ilnur Radikovich Suleymanov (Scholar Express Journals, 2025)
This study investigates the integrative potential of the real economy in strengthening the banking sector in Uzbekistan. It highlights the dynamic interplay between industrial growth and financial services expansion, analyzing sectoral trends from 2020 to 2023 and forecasting through 2025. Using statistical data and projections from international financial institutions, this paper evaluates the mutual reinforcement between industrial, construction, and service sectors and the financial system, emphasizing the role of modernization, technological development, and structural reforms in enhancing this synergy
Keywords: Uzbekistan; real economy; banking system